Perancangan dan Implementasi Sistem Informasi Manajemen Penilaian Siswa Berbasis Web pada SMP Tahfidz Assyifa Al-Islami Parung - Rizki Abdul Karim; Abdul Ghofur; Chaeruddin Ramadhan; Hidayatullah Al Islami (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The development of information technology requires educational institutions to adopt digital systems in academic processes. SMP Tahfidz Assyifa Al-Islami Parung faces problems in recording and processing student grades manually, which are prone to errors and inefficiencies. This study aims to design and implement a web-based student assessment management information system to assist teachers in inputting, managing, and reporting grades. The system is developed using UML-based modeling and built with PHP, MySQL, and the Bootstrap framework. Implementation results show the system improves the efficiency, accuracy, and accessibility of student grade data. With this system, the academic evaluation process becomes faster and more transparent.